Investigating the Status and Errors of Search Strategy in Persian Medical Systematic Reviews and Meta-Analyses - Mahsa Ghasemian; Mohammad Karim Saberi; Mohammad Reza Amiri (International Journal of Information Science and Management)
Search strategy is one of the main criteria for quality assessment of meta-analyses and systematic reviews. This descriptive-analytical research aims to investigate the status and errors of search strategy in Persian medical meta-analyses and systematic reviews indexed in The Scientific Information Database (SID) until February 2023. A total of 421 articles were identified. A checklist containing 31 items was used to collect the data. It is established based on a similar study and getting experts' opinions to check the status of search strategy reporting in articles and collaboration of librarians. Using SPSS version 25, descriptive statistics was used to analyze the data. The results showed that 15.9% of articles reported the systematic search strategy; 97.1% of the reviewed articles did not mention the collaboration of librarians in formulating the search strategies. 17.3% of articles had complete comprehensiveness regarding the number of databases used. The most common errors in PubMed and Scopus were “Not using controlled keywords,” but in the Web of Science database, it was “Not using all the concepts and keywords related to the subject”. The final result is that in most Persian medical meta-analyses and systematic reviews, the search strategy does not have a proper status in terms of reporting in the article and errors, which can influence the recall and reduce the quality of this type of article. Not having enough skills in how to search effectively and not using librarians in searching can be the cause of this situation.